The Use of Virtual Reality in Pharmacy Education in Hong Kong: Lessons Learnt - Li, Joyce T. S.; Ng, Enoch E. N.; Lee, Vivian W. Y. (Frontiers in Education, 2021)
Virtual reality (VR) refers to an artificial environment which is experienced through sensory stimuli (such as sights and sounds) provided by a computer and in which one's actions partially determine what happens in the environment (Merriam-Webster.com Dictionary, Merriam-Webster, 2020). In recent years, VR is increasingly used in different fields, and its role in medical practice is expanding quickly (Darekar et al., 2015; Chirico et al., 2016). One important feature of VR technology is its reproducibility (Ramnanan and Pound, 2017; Cao and Cerfolio, 2019). Practitioners can rehearse a procedure on a virtual patient or simulated tissue as many times as they wish before performing it on real patients. In medical education, VR allows students to see through body tissues and visualize the underneath areas (Cao and Cerfolio, 2019; Yu et al., 2019; Siyar et al., 2020). Practice experience is an essential element in pharmacy education (Teramachi et al., 2018). It is effective in boosting students' communication skills and problem-solving skills, which are both crucial for the provision of patient-centered care in a team-based approach (Lang et al., 2019). Unfortunately, actual practice experience can be limited by various factors, such as the policies at attachment sites, patients' preference, and availability of teaching staff (Wartman, 2019; Shrestha et al., 2020). Therefore, institutions are looking for alternative channels for students to practice their skills. One strategy is to adopt simulated patient cases (Kurup et al., 2017; Willemsen-Dunlap et al., 2018; Silva et al., 2019). In this paper, we share our experience of using VR learning tools in pharmacy education in a Hong Kong university. We will discuss the opportunities, challenges, and suggestions for future development of VR in pharmacy education.